2021
DOI: 10.1038/s41598-021-91533-4
|View full text |Cite|
|
Sign up to set email alerts
|

Lipid profile dysregulation in opium users based on Fasa PERSIAN cohort study results

Abstract: One of the main health problems in many societies is the increased opium abuse, which was found to be correlated with many problems like cardiovascular disease. This study aimed to evaluate the correlation of opium use with blood lipoproteins as the risk factor of CVD. This was a cross-sectional study conducted on participants of the first phase of the PERSIAN Cohort study who were aged between 35 and 70 years old. Demographic characteristics; history of smoking, alcohol, and opium consumption; medical history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…The ndings of our study showed that the prevalence of opium use is 16%, which is more than the study of Fallahzadeh et al (19) and in line with the results of the cohort studies conducted in the north (10) and lower than south of Iran (20).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The ndings of our study showed that the prevalence of opium use is 16%, which is more than the study of Fallahzadeh et al (19) and in line with the results of the cohort studies conducted in the north (10) and lower than south of Iran (20).…”
Section: Discussionsupporting
confidence: 92%
“…In other studies, the role of ethanol in increasing triglyceride levels has been mentioned, so that in a clinical trial study that was conducted on healthy people and people with hypertriglyceridemia, it was shown that people who drank moderate amounts of ethanol three times a day, saw their plasma triglyceride levels increase signi cantly (40), which is in line with the results of our study. It has been mentioned in other studies that alcohol increases triglyceride levels (20,41). Previous studies in line with this study have shown that triglycerides are signi cantly higher in obese people (20,42).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations